The 'Named Person' debate: the case for - Mike Burns (Scottish Journal of Residential Child Care)
The term GIRFEC gets banded around so much these days that it has become just another piece of obscure professional jargon. What it represents is far better served by giving it its full title: Getting It Right For Every Child. In that title the word 'every' is critical, because it captures a universal aspiration to make Scotland a better place to grow up for all children, while at the same time emphasising that we must do more for the most vulnerable, marginalised and neglected children. Social Work Scotland's Children and Family's Committee has a direct line of sight to these children and communities, and we are confident that Getting it Right For Every Child - and in particular the Named Person -